Psychological challenges for young officers in assistance operations - Chalupsky Thomas (2017)
Psychological challenges for young officers in assistance operations The present thesis deals with psychological challenges for young officers with which they can be confronted in assistance operations. To give the reader of the thesis a better understanding for assistance operations inside the boundaries of Austria, the author gives a short overview about the national and international legal bases. This chapter is very important because it is the cornerstone under which circumstances the Austrian Armed Forces can be deployed inside the boundaries of Austria. Therefore it was possible to explain both, national and international law. The second part of the present thesis deals with assistance operations which took part in Austria in the past. For a better understanding, the author explained several very important words and phrases in advance. It is very important to give a short overview of assistance operations which took place in the past that the reader gets an imagination of what the AAF already did and what for they can be used. The third part (chapter 4) is the main part of the thesis and deals with psychological challenges which young officers of the AAF can get confronted in assistance operations. It was very important for the author to describe his own experiences which he gained during his service in assistance operations and military missions abroad. The author describes the roll of the soldier in his/ her family and how important preparation for an assistance operation is. He also mentioned how private issues can turn into serious problems during an assistance operation and which points exist on which the young officer can turn to during an operation in case of psychological challenges. But not only the preparation in advance and the psychological challenges during an assistance operation are described, also the possibility that psychological problems can be turn up after an assistance operation. The fourth part concludes the thesis with possible economic consequences for the republic of Austria in case a young officer suffers of psychological problems before, during or after an assistance operation. For a better understand the author not only mentioned the costs for the medical treatment, also for the transport and how much a young officer costs from the bottom to the top.